Differential Sintering and Self-Stress Effects on YSZ Ionic Conductivity - Goulart, Celso A. [UNESP] (2023)
Thermomechanical stress simulations are combined with experimental tests to assess the effects of rigid inclusions on the sintering of 8 mol% yttria-stabilized zirconia (8YSZ) green compacts and the phenomena of restricted and differential sintering on microstructure development and electrical properties are investigated. Rigid inclusions of sintered ceramic particles with different shapes (spherical and jagged) and compositions (alumina, 3YSZ, and 8YSZ) are added in different volume fractions (1, 5, and 15 vol%) to 8YSZ commercial powders, which are formed by isostatic pressing and sintered by conventional method. Restricted and differential sintering effects are observed in the development of the microstructure varying in function of volume fraction, shape, structural composition, and thermomechanical properties of the inclusions, resulting in different combinations of tensile and compressive strain states in the matrix, and varying electrical behaviors. The addition of 1 vol% of 8YSZ irregular rigid inclusions leads to an increase of 36% in total electrical conductivity and a 33% increase in power density under solid oxide fuel cells operation conditions compared to samples without inclusions.